Monopsony power and minimum wages - Gomes, Henrique Manuel Da Silva (2020)
In this study, we perform an assessment of the level of monopsony power in the Portuguese la-bor market by building on the existing dynamic monopsony literature. After producing firm-levelestimates of the labor supply elasticity, we found evidence of employers having a large degree ofmarket power in the labor market. Furthermore, we perform an assessment of the joint impact ofmonopsony power and the minimum wage on the employment level of the labor market. Our find-ings confirm the predictions made in the literature. We conclude that an increase in minimum wagewill increase the employment level of an employer with a high degree of monopsony power.